Dirofilaria immitis in pinnipeds and a new host record - Alho, Ana Margarida; Marcelino, Inês; COLELLA, VITO; Flanagan, Carla; Silva, Nuno; Correia, Jorge Jesus; LATROFA, MARIA STEFANIA; OTRANTO, Domenico; Madeira De Carvalho, Luís (Parasites & Vectors, 2017)
Background: Dirofilaria immitis is a mosquito-borne pathogen that is spreading worldwide, and the associated infection (i.e. dirofilariosis) is becoming a threat to animals and humans living in endemic areas. Little is known about the occurrence and risk of infection of D. immitis in pinnipeds. Here we report dirofilariosis by D. immitis in several pinniped species kept in captivity in Portugal. Methods: Animals were housed in an oceanographic park located in Algarve, southern Portugal, a geographical area endemic for canine dirofilariosis. To assess the occurrence of D. immitis, blood was collected from the park's resident pinniped population, which consisted of 16 animals (5 common seals Phoca vitulina, 2 grey seals Halichoerus grypus, 3 California sea lions Zalophus californianus and 6 South African fur seals Arctocephalus pusillus pusillus). Dirofilaria immitis nematodes were detected by real-time PCR and by the presence of circulating antigens. In addition, modified Knott's technique was performed to detect circulating microfilariae. Necropsies and histopathological examination of two animals which died during the study were also conducted. Results: Out of the 16 pinnipeds housed at the park, seven (43.8%) were positive for D. immitis by real-time PCR (3 P. vitulina, 2 Z. californianus and 2 A. p. pusillus), two of which (P. vitulina) were also positive for the nematode's antigen. Additionally, D. immitis microfilariae were detected in one A. p. pusillus. Furthermore, several D. immitis specimens were retrieved from the right ventricle and pulmonary arteries at the necropsy of one P. vitulina and one A. p. pusillus. Conclusions: This study provides new epidemiological data on D. immitis infection in pinnipeds diagnosed through clinical, molecular and pathological findings. Additionally, the South African fur seal is herein reported as a new host for this zoonotic filarioid. The situation herein described could also occur in other parks located in areas where canine dirofilariosis is endemic. Active ...